The Effectiveness of Focus on Forms and Focus on Form Instruction on Productive Vocabulary Knowledge - Welda Yusriana (Graduate Program, University of Islam Malang, 2019)
AbstractThe aim of the study was to investigate the effectiveness of Focus on Forms (FonFs) and Focus on Form (FonF) instruction on productive vocabulary knowledge. Being designed in quasi-experimental, 65 students in the classes of first grade of junior high school were divided into two different groups receiving different instruction. FonFs group as Experimental group receiving instruction through present-practice-produce (PPP) task, while Control (FonF) group receiving instruction through Dictogloss task. These two group were proved on different level of productive vocabulary knowledge before treatment by the score of productive vocabulary level test, the scores than became pretest score. After the treatment, a set of test was given to get the posttest score. To achieve the purpose of this study, the scores of the productive vocabulary test then analyzed using ANCOVA in SPSS 20. The result of this study indicated that FonFs and FonF instruction affected students’ productive vocabulary knowledge ability. It concluded that Form-Focused instruction is claimed to be indispensable for productive vocabulary knowledge. Keywords: focus on forms instruction, focus on form instruction, productive vocabulary knowledge